Cover Image, Volume 37, Issue 13. (29th December 2017) - Werner, Heron; Lopes, Jorge; Ribeiro, Gerson; Jésus, Nilson Ramires; Santos, Gildasio Rocha; Alexandria, Helenara Abadia Ferreira; Ruano, Rodrigo; Araujo Júnior, Edward
Abstract : Composite image of a three‐dimensional virtual reconstruction of fetal urinary tract from magnetic resonance imaging scan data at coronal (left) and three‐dimensional virtual cystoscopy showing the urethral lumen and the dilated ureter (right). DOI:10.1002/pd.5188 . From Werner et al., in this issue.